Du ségrégationnisme à l'inclusion : les initiatives éducatives des minorités noires en Nouvelle-Écosse - Nguirane, Cheikh (Initio, 2014)

La diaspora noire au Canada : sociohistoire d’une minorité racialisée et dynamiques contestataires - Nguirane, Cheikh (Archipélies, 2022)

“As if we were all struggling together”: Black intellectual traditions and legacies of gendered violence - Zellars, Rachel B. (Women's Studies International Forum, 2019)
In North America, both Canada and the United States, violence against Black women has too often been historically displaced in the context of Black radical intellectual and organizing traditions. This paper attempts to account for the costs of this legacy and proposes a new model for Black intellectual traditions and organizing—that is, one that centres violence against women as a fundamental syntax within its organizing politic.

He ‘is supposed to have with him forged Certificates of his Freedom, and Passes’: Slavery, (Im)mobility, and the Creolized Counter-Knowledge of Resistance - Nelson, Charmaine A. (Global Intellectual History, 2023)

La Maison d'Haïti: Haitian Stories of Resistance and Black Diasporic Activism in Montréal, 1972—1986 - Rochat, Désirée (Histoire sociale, 2022)

The Demise of a Black Organization: The Home Service Association (1921–65) - Knight, Melanie (Canadian Journal of History, 2020)

A "tone of voice peculiar to New-England": Fugitive Slave Advertisements and the Heterogeneity of Enslaved People of African Descent in Eighteenth-Century Quebec - Nelson, Charmaine A. (Current anthropology, 2020)

Acts of Resistance Black Men and Women Engage Slavery in Upper Canada, 1793-1803 - Cooper, Afua (Ontario History, 2019)